KEAMANAN TEH GAHARU (Aquilaria malaccencis Lamk ) DARI POHON INDUKSI TERHADAP TOKSIK ORAL - Batubara, Ridwanti; Surjanto, Surjanto; Purba, Marsen (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
Leaves aloes (Aquilaria malaccencis Lamk) used the farmer as a drink that in pour (tea). The result of that tea aloes have a very strong antioxidant activity. The problem are the aleo tea from tree induction safety of consume. This study aims to determine the symptoms of toxic posed of product tea aloes induction. The research method refers to the Guidance of Toxicity Non-Clinic Test in Vivo, Badan POM RI, 2011. Results showed that not found toxic symptoms in all treatment of male and female mice, safe for consumption.